2019
DOI: 10.1002/gj.3664
|View full text |Cite
|
Sign up to set email alerts
|

An ensialic volcanic arc along the northwestern edge of Palaeotethys—Insights from the Mid‐Triassic volcano‐sedimentary succession of Ivanščica Mt. (northwestern Croatia)

Abstract: This work aims to unveil the origin, geodynamic significance, and diagenetic history of pyroclastites and associated chert documented within the Upper Anisian volcanosedimentary succession of the Ivanščica Mt. in Central Europe. An abundance of pyroclastic material points to polyphase volcanic activity and deep-water sedimentation along the rim of an oceanic realm. Radiolarian-based dating revealed Illyrian age of chert intercalated with pyroclastites. The latter are largely vitro-crystalloclastic and were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…Similar effusive and pyroclastic rocks found elsewhere in the mountains of NW Croatia are all interbeded with Middle Triassic marine sediments (e.g. Goričan et al, 2005;Halamić, 1998;Marci et al, 1982Marci et al, , 1984Šimunić and Šimunić, 1979;Šimunić, 1992;Slovenec et al, 2020). The volcanic activity of that period was characterized by submarine andesite to basaltic lava flows accompanied by multiple explosive eruptions of volcanic material.…”
Section: Geological Settingmentioning
confidence: 65%
See 4 more Smart Citations
“…Similar effusive and pyroclastic rocks found elsewhere in the mountains of NW Croatia are all interbeded with Middle Triassic marine sediments (e.g. Goričan et al, 2005;Halamić, 1998;Marci et al, 1982Marci et al, , 1984Šimunić and Šimunić, 1979;Šimunić, 1992;Slovenec et al, 2020). The volcanic activity of that period was characterized by submarine andesite to basaltic lava flows accompanied by multiple explosive eruptions of volcanic material.…”
Section: Geological Settingmentioning
confidence: 65%
“…The Middle Triassic volcanism of NW Croatia is represented by submarine flows of basaltic to rhyolitic lavas and explosive eruptions of pyroclastic material (e.g. Goričan et al, 2005;Šimunić, 1992;Slovenec et al, 2020;and references therein). Previous stratigraphic studies identified two volcanic events.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations